STUDI PERBANDINGAN JUMLAH IKAN LELE DAN KULIT PISANG PADA PEMBUATAN KERUPUK â€œLEKUPIâ€ - Herawati, Yeni; Dasir, Dasir (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2013)
This study aimed to study the ratio of a banana skin and catfish on making crackers "lekupi". This research has been held in Laboratory Faculty of Agriculture, University of Muhammadiyah Palembang in October 2012 to February 2013. This research used Randomized Block Design (RBD), which compiled non-factorial consisting of four combinations of treatment and repeated five times, with each treatment factor P1 (50% banana skin: catfish, 10%: 40% starch), P2 treatment (40% banana skin: catfish, 20%: 40% starch), treatment P3 (20% banana skin: catfish, 40%: 40% starch), and P4 treatment (10% banana skin: catfish 50%: 40% starch). Parameters observed for chemical analysis covering the water content and protein content. While organoleptic include flavor and color to the hedonic test and the level of crispness to the rank test and physical test includes volume expansion. The results showed that the ratio of the number of catfish and banana peels are very real effect on the moisture content, protein content and volume expansion. Assessment of organoleptic test showed that the ratio of the number of catfish and banana peels significantly affect the flavor, color and crispness Crackers "Lekupi". The results showed that treatment of P4 has the lowest water content (10.617%), the highest protein content (14.74%), and highest volume expansion (6.253 x 100%). While in treatment P1 has the highest water content (12.405%), the lowest protein content (5.04%) and the lowest volume expansion (3.212%). In organoleptic treatment P2 has color, and flavor with the highest level of preference with the average value of 3.75 (criterion rather liked), 3.66 (criterion rather liked). Meanwhile, highest level of crispness found in P4 treatment with an average value of 1.42 (the criteria are very crisp at all).